Heart Rate Variability and Procedural Outcome in Catheter Ablation for Atrial Fibrillation. Issue 1 (24th September 2013) - Seaborn, Geoffrey E.J.; Todd, Keith; Michael, Kevin A.; Baranchuk, Adrian; Abdollah, Hoshiar; Simpson, Christopher S.; Akl, Selim G.; Redfearn, Damian P.
<x xml:space="preserve">Abstract</x> Introduction In patients with normal hearts, increased vagal tone is associated with onset of paroxysmal atrial fibrillation (AF). Vagal denervation of the atria renders AF less inducible. Circumferential pulmonary vein isolation (CPVI) is effective for treating paroxysmal and persistent AF, and has been shown to impact heart rate variability (HRV) indices, in turn, reflecting vagal denervation. We examined the impact of CPVI on HRV indices, and evaluated the relationship between vagal modification and AF recurrence. Methods Electrocardiogram recordings were collected from 83 consecutive patients (63 male, 20 female, age 56.9 ± 9.3 years) undergoing CPVI for paroxysmal (n = 56) or persistent (n = 27) AF. Recordings were obtained over 10 minutes preprocedure, and at intervals up to 12 months. Antiarrhythmic medications were suspended prior to CPVI, and were resumed for 3 months following. Success was defined as no recurrence of atrial arrhythmia lasting longer than 30 seconds. Results In patients with successful procedures (n = 56, 42 paroxysmal, 14 persistent), HRV indices were significantly altered, with respect to preprocedure levels, over a sustained period. However, patients with recurrence (n = 27, 14 paroxysmal, 13 persistent) demonstrated similar HRV to their preprocedure levels over the follow‐up period. Conclusion Our results suggest that patients experiencing recurrence after a single CPVI have HRV attenuated by the procedure only intermittently, whereas patients with one successful CPVI experience a sustained change. A short‐term HRV recording is a convenient and potentially important marker for recurrence of atrial arrhythmia in a population undergoing CPVI.